Peran Kyai Dalam Membina Akhlak Santri Di Pondok Pesantren Al-Muinah Darul Ulum Desa Simpangan Kecamatan Wanayasa - Imam Tabroni; Asep saipul Malik; Diaz Budiarti (Jurnal Pendidikan, Sains Sosial, dan Agama, 2021)
Islamic boarding schools as educational institutions play an important role in fostering the morals of students. Kyai has the obligation to foster students to have good morals at the Darul Ulum Al-Muinah Islamic boarding school. The purpose of the study was to find the Kyai program in fostering the morals of students. This research uses descriptive qualitative research. The research focuses on Kyai and santri to find out the role of Kyai in fostering the morals of students at the boarding school. The steps of data collection are through observation, interviews, and documentation. Data reduction, data display, and data verification. Research results: (1). The Kyai program at Darul Ulum Al-Muinah Islamic Boarding School includes daily, weekly and monthly programs. (2). Kyai is able to foster the character of students, although not entirely, (3). Kyai coaching methods: Lecture method, role model and life skills. (4). Supporting factors include: the strategic location of the Islamic boarding school, encouragement from alumni, competent teaching staff, community support and the village government. The inhibiting factor is that the pesantren does not yet have a good management system, and still requires financial assistance.(5). Kyai always consult with the management, analyze every problem, determine the solution. And how to strengthen support by linking the pesantren's internal team, both families and boarding school administrators and building relationships with various stakeholders.